(untitled) (Journal of Geography and Environmental Management, 2019)
In the article is analyzes long-term fluctuations in the runoff of the Shu-Talas river basin. In the irver basin connection with the lack of data in the series of observations for the selected calculation period, the hydrological data of the series were restored by using the method of recalculated analogs. The homogeneity series of the river basin was estimated by using the modern StokStat program, as well as Student, Fisher, Wilcoxon criterias. Long-term runoff fluctuations were determined by various methods, in particular, the difference integral curves, the number of series, the generalization of years of different probability. Fluctuations in the runoff are calculated by the method of the probability of occurrence of a average water ages. The study of fluctuations in river runoff is a very difficult task, it has great scientific and practical significance. Long-term fluctuations in river runoff directly depend on the flowforming factors, and the rivers have been classified into several types of feeding of rivers. For river basins covering large areas and located on different physical and geographical conditions, the study of cyclic fluctuations in the runoff layer was carried out on the basis of observation materials. Evaluation of long-term fluctuations of the Shu-Talas river basin is of great importance for water supply of settlements, water management facilities, recreational areas of the region.